2022
DOI: 10.1002/pc.26962
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis with grey relational analysis–analytic hierarchy process‐based hybrid optimization to analyze the effect of graphene nanoparticle reinforced ultra‐high molecular weight polyethylene/n‐HAp for hip joint

Abstract: Ultra‐high molecular weight polyethylene (UHMWPE) is utilized in hip joints because of its high impact strength, outstanding fracture resistance, near‐zero moisture absorption, superior chemical inertness, and lower coefficient of friction than other polymers. However, because of the high melt viscosity of UHMWPE, the melt state approach gives unsatisfactory mechanical strength results. In this research, composite materials are fabricated by heat‐assisted compression molding having graphene nanoplatelets (GNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…[1][2][3][4] Among them, it is a simple and effective way to incorporate nanofillers to optimize the structure and properties of UHMWPE. [5][6][7] Pang et al discovered that the incorporation of a small quantity of graphene oxide (GO) greatly decreased the wear rate and lowered the friction coefficient of UHMWPE composites by reducing the plastic deformation of polymer chains. 8 Liu et al demonstrated that boron carbide particles could reduce the shear damage and improve the wear resistance of UHMWPE during friction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Among them, it is a simple and effective way to incorporate nanofillers to optimize the structure and properties of UHMWPE. [5][6][7] Pang et al discovered that the incorporation of a small quantity of graphene oxide (GO) greatly decreased the wear rate and lowered the friction coefficient of UHMWPE composites by reducing the plastic deformation of polymer chains. 8 Liu et al demonstrated that boron carbide particles could reduce the shear damage and improve the wear resistance of UHMWPE during friction.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain improved mechanical and wear resistance for UHMWPE, various strategies have been proposed and developed, including surface coating, cross‐linking, irradiation, and blend modification 1–4 . Among them, it is a simple and effective way to incorporate nanofillers to optimize the structure and properties of UHMWPE 5–7 . Pang et al discovered that the incorporation of a small quantity of graphene oxide (GO) greatly decreased the wear rate and lowered the friction coefficient of UHMWPE composites by reducing the plastic deformation of polymer chains 8 .…”
Section: Introductionmentioning
confidence: 99%